2013
DOI: 10.1016/j.exphem.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of human bone marrow adipocytes

Abstract: Adipocytes are a cell population largely located in the human bone marrow cavity. In this specific microenvironment where adipocytes can interact with a variety of different cells, the role of fat is mainly unknown. To our knowledge, this report is the first to characterize mature adipocytes isolated from human bone marrow (BM-A) molecularly and functionally to better understand their roles into the hematopoietic microenvironment. Healthy BM-A were isolated after collagenase digestion and filtration. We studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 30 publications
2
54
0
1
Order By: Relevance
“…Moreover, in line with these results, the dedifferentiated fat cells displayed long telomeres (11.5 6 0.7 kb) [37]. Thus, telomere length and the absence of karyotype alterations demonstrated that these cells were not susceptible to malignant transformation.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, in line with these results, the dedifferentiated fat cells displayed long telomeres (11.5 6 0.7 kb) [37]. Thus, telomere length and the absence of karyotype alterations demonstrated that these cells were not susceptible to malignant transformation.…”
Section: Discussionsupporting
confidence: 68%
“…This also prompts the question – are all MAT-appearing cells within the bone marrow actually adipocytes? Expression of key adipogenic transcription factors Pparg , Cebpa , and Cebpb in isolated MAT cells from healthy animals supports this identity [5,43]. However, the storage of marrow lipid in non-MAT populations, especially in states of disease, has not been thoroughly explored.…”
Section: Mat Versus Other Adipose Tissuesmentioning
confidence: 99%
“…MAT is also intimately associated with the blood-forming marrow. Primary human MAT adipocytes, purified from the iliac crest, have the ability to support differentiation of CD34+ hematopoietic progenitor cells in vitro [43]. However, in vivo evidence in mice suggests that MAT adipocytes are predominantly negative regulators of the hematopoietic microenvironment, inducing both quiescence and loss of progenitor cells [15].…”
Section: Mat Versus Other Adipose Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may be related more to the nature rather than the quantity of marrow adipose. For example, during puberty and with fracture repair processes, marrow fat exhibits a brown adipocyte-like phenotype characterized by the expression of brown adipocyte transcription factors (e.g., PR domain containing 16 (Prdm16) and Forkhead Box C2 (FoxC2)) and marker genes (e.g., PGC1 α , deiodinase 2 (Dio2), beta-3-adrenergic receptor (β3AR), and uncoupling protein 1 (UCP1)) [1, 4, 63, 64]. It is generally believed that marrow adipocytes exhibiting brown adipocyte-like phenotype contribute to a microenvironment favorable for osteogenesis by providing the necessary energy balance, adaptive thermogenesis, and/or by releasing pro-osteogenic factors such as insulin-like growth factor 1 (IGF1) and leptin [1, 4, 64, 65].…”
Section: Does Clinical Evidence Support a Role For Adipocytes In Skelmentioning
confidence: 99%